2003
DOI: 10.1023/a:1026269804938
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The genetic structure of earthworm (Lumbricus rubellus) populations from plots (N = 3) contaminated by sewage sludge (containing Cd, Cu, Pb, Zn) and reference plots (N = 3) was compared. Earthworms (N = 30-40 per plot) were collected during May 2000 and electrophoretic analyses were used to assess genetic variation at three polymorphic loci (GPI, LAP, PGM). Allele and genotype frequencies for GPI and PGM differed significantly between sludge and reference populations. Sludge populations were characterized by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…There are examples in the wild of selective effects of chemicals on populations. Numerous field studies have shown historical metal pollution has imposed selection on exposed wildlife populations, with directional evolution in neutral marker loci along spatial and temporal gradients of exposure (Klerks & Weis 1987;Groenendijk et al 2002;Klerks 2002;Peles et al 2003). Increasing levels of metal contamination are often associated with reduced genetic variation at the population level.…”
Section: The Genetic Basis For Chemical Resistancementioning
confidence: 99%
“…There are examples in the wild of selective effects of chemicals on populations. Numerous field studies have shown historical metal pollution has imposed selection on exposed wildlife populations, with directional evolution in neutral marker loci along spatial and temporal gradients of exposure (Klerks & Weis 1987;Groenendijk et al 2002;Klerks 2002;Peles et al 2003). Increasing levels of metal contamination are often associated with reduced genetic variation at the population level.…”
Section: The Genetic Basis For Chemical Resistancementioning
confidence: 99%
“…The effect of environmental contaminants on population genetic structure has been the subject of many recent studies ( ). Environmental contamination can influence population genetic structure via genetic bottlenecks, genetic adaptation to contaminants, alternations in gene flow, or enhanced mutation rate (see refs 27−30 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…The use of population genetic data to investigate effects of chronic contaminant exposure has proven effective in studies representing a diversity of organisms and ecological settings. Molecular genetics is a powerful tool to identify reductions in genetic diversity (Murdoch and Hebert 1994), contamination-induced natural selection (Bridges and Semlitsch 2001; Foré et al 1995a, 1995b; Peles et al 2003; Theodorakis and Shugart 1997), ecological sinks (Baker et al 2001; Matson et al 2000; Theodorakis et al 2001), and increased mutation rates (Ellegren et al 1997; Forster et al 2002; Somers et al 2002). The application of evolutionary or population genetic approaches to problems in ecotoxicology has been reviewed in several articles (Belfiore and Anderson 2001; Bickham et al 2000; Bickham and Smolen 1994; Hebert and Luiker 1996; Van Straalen and Timmermans 2002).…”
mentioning
confidence: 99%